Experimental and theoretical investigation on rotodynamic characterization of hybrid porous tilting pad bearings. (1st February 2022) - Wu, Yihua; An, Lin; Feng, Kai; Cao, Yuanlong; Guan, Hanqing
Highlights: The test rig is set up and the rotor accelerates up to 40 krpm . The supply pressure of each pad is monitored separately. A nonlinear dynamics model that considers film pressure and rotor motions is established. The influence of supply pressure, mass imbalance on system stability is explained. Abstract: Porous journal gas bearings, which offer advantages of high load capacity and good stiffness compared to other types of hydrostatic gas bearings, will meet instability issues at high rotational speeds. Hybrid porous tilting pad bearings (HPTPBs) provide a possibility as a rotor supported in high-speed Turbomachinery. This study presents an experimental investigation of the dynamic responses of a rigid rotor supported with two HPTPBs. The rotor was successfully accelerated to 40 krpm. The supply pressure ratio of each pad is monitored separately, and the influence of the separate gas supply on the dynamic response is analyzed. Rotor dynamic tests with different unbalance mass and different supply pressure ratios were carried out. A mathematical model with the consideration of airflows in the porous materials and bearing clearance, pad motion, rotor motion, unbalance force were presented. Prediction results are accorded well with the test results.